Glial Cells and Integrity of the Nervous System - Eugenin-Leon, J (Springer New York LLC, 2016)
Today, there is enormous progress in understanding the function of glial cells, including astroglia, oligodendroglia, Schwann cells, and microglia. Around 150 years ago, glia were viewed as a glue among neurons. During the course of the twentieth century, microglia were discovered and neuroscientists’ views evolved toward considering glia only as auxiliary cells of neurons. However, over the last two to three decades, glial cells’ importance has been reconsidered because of the evidence on their involvement in defining central nervous system architecture, brain metabolism, the survival of neurons, development and modulation of synaptic transmission, propagation of nerve impulses, and many other physiological functions. Furthermore, increasing evidence shows that glia are involved in the mechanisms of a broad spectrum of pathologies of the nervous system, including some psychiatric diseases, epilepsy, and neurodegenerative diseases to mention a few. It appears safe to say that no neurological disease can be understood without considering neuron-glia crosstalk. Thus, this book aims to show different roles played by glia in the healthy and diseased nervous system, highlighting some of their properties while considering that the various glial cell types are essential components not only for cell function and integration among neurons, but also for the emergence of important brain homeostasis. © Springer International Publishing Switzerland 2016.